Accrual-Based Accounting Information System For Financial Compliance Monitoring - I Nyoman Darma Kotama; Putu Sugiartawan; I Dewa Ayu Sri Murdhani (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2026)
Small and medium-sized enterprises (SMEs) often face challenges in implementing efficient and accurate financial reporting systems, primarily due to the limitations of manual accounting processes. These challenges lead to errors, delays, and compliance issues, which hinder timely decision-making and financial transparency. This research proposes the development and evaluation of an accrual-based Accounting Information System (AIS) designed to address these issues by automating financial reporting and compliance monitoring. The motivation behind this study is to improve the financial management practices of SMEs by providing a reliable system that ensures accurate financial reporting and real-time compliance monitoring. The main contribution of this research is the design of an AIS that integrates key financial functions, such as transaction processing, accrual calculations, and compliance checks, to streamline financial operations. Evaluation results from case studies indicate that the system significantly reduced reporting errors by 50%, enhanced compliance accuracy by 25%, and decreased report generation time by 40%. Despite these successes, challenges remain in system integration with legacy accounting software and handling complex financial transactions. Future work will focus on enhancing the scalability of the system, integrating advanced machine learning techniques for predictive financial analysis, and improving the integration process to allow for broader implementation in diverse business contexts. Additionally, the development of a mobile application to improve accessibility to financial reports and compliance alerts will be explored.